Expression profile of long non-coding RNAs is altered in endometrial cancer - Yang, Lin (Int J Clin Exp Med, 2015)
This study was to uncover the role of long non-coding RNA (lncRNA) in the process of endometrial cancer (EC) development using microarray technique to obtain the expression profiles of lncRNAs in EC and its adjacent normal tissues. A total of 45 pieces of pathologically-proven EC tissues were used in this study. All samples were frozen in liquid nitrogen immediately after resection and stored at -80°C for future use. The detection of lncRNA and transcripts was conducted using microarray analysis. To understand the biochemical function of lncRNA, bioinformatics analyses (gene ontology and pathway analyses) were performed. To further investigate the relationship between lncRNAs and EC, subgroup analysis was conducted. In order to validate the consistency of the lncRNAs with microarray data, qRT-PCR was performed. In this study, 30586 lncRNAs and 26109 transcripts (fold change ≥ 2.0) were found in the tested EC. In particular, compared with normal tissues, 4010 the lncRNA were up-regulated, and 3350 of them were down-regulated. Seven of the lncRNAs were in accordance with microarray data in qRT-PCR. Among these lncRNAs, 3 were up-regulated and 4 were down-regulated. Furthermore, pathway analysis revealed that 24 pathways were correlated to the up-regulated transcripts, while 27 pathways were associated with the down-regulated transcripts. Our study demonstrated that the expressions of a large amount of lncRNAs were altered in EC in comparison to normal tissues, suggesting that lncRNAs could potentially serve as a diagnostic biomarker that is beneficial for the diagnosis and therapy of EC.